2020
DOI: 10.3389/fonc.2020.00615
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-coding RNA LINC02195 as a Regulator of MHC I Molecules and Favorable Prognostic Marker for Head and Neck Squamous Cell Carcinoma

Abstract: The loss of major histocompatibility complex class I (MHC I) molecules is an important mechanism by which cancer cells escape immunosurveillance in head and neck squamous cell carcinoma (HNSCC). Several long non-coding RNAs (lncRNAs) have been implicated in immune response and regulation including antigen processing and presentation. However, few studies on lncRNAs regulating MHC I expression in HNSCC have been conducted. In this study, MHC I related lncRNAs were identified from the The Cancer Genome Atlas (TC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…ncRNAs can also be positive regulators of MHC I. For example, in head and neck squamous cell carcinomas, expression of the lncRNA, lnc02195, increases MHC I expression and is associated with a better prognosis ( 208 ). In nasopharyngeal carcinomas miR9 expression increases expression of MHC I molecules and TAP1 ( 209 ).…”
Section: Loss Of the Mhc I Antigen Presentation Pathway In Cancers Thmentioning
confidence: 99%
“…ncRNAs can also be positive regulators of MHC I. For example, in head and neck squamous cell carcinomas, expression of the lncRNA, lnc02195, increases MHC I expression and is associated with a better prognosis ( 208 ). In nasopharyngeal carcinomas miR9 expression increases expression of MHC I molecules and TAP1 ( 209 ).…”
Section: Loss Of the Mhc I Antigen Presentation Pathway In Cancers Thmentioning
confidence: 99%
“…The loss of major histocompatibility complex I (MHC I) molecules is an important mechanism for HNSCC cells to evade immune surveillance. However, LINC02195 is a crucial regulator of MHC I molecules ( 45 ). Moreover, novel lncRNA SFTA1P promotes tumor growth by downregulating miR-4766-5p via the PI3K/AKT/mTOR signaling pathway in hepatocellular carcinoma ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Li et al also found out that silencing LINC02195 expression causes a decrease in the level of MHC I molecules and definitely proved that patients with high expression of this lincRNA have a better prognosis. Further research indicated that this lincRNA is immune-related due to its significant correlation with the T cell receptor pathway, chemokines (class I and II), and cytokines [91]. The discovered association with lymphocytes T suggests better infiltration of tumor tissue, which leads to the positive response to immunotherapy and better prognosis, not only in HNSCC but in many different cancers [91][92][93].…”
Section: Known Lincrna Biomarkers In Hnsccmentioning
confidence: 96%
“…Long non-protein-coding RNA 2195 (LINC02195) is closely associated with major histocompatibility complex class I (MHC I) molecules, whose lack of function leads to the mechanism of escaping immunosurveillance by tumor in HNSCC [91,92]. Analysis of LINC02195 expression patterns showed significantly higher lincRNA levels in HNSCC tumor samples than in cell lines derived from dysplastic tissue or normal mucosa.…”
Section: Known Lincrna Biomarkers In Hnsccmentioning
confidence: 99%